Looking for Lincoln in Illinois : Lincoln's Springfield - Andreasen, Bryon C. (Book collections on Project MUSE., 2015)
Presenting fifty Abraham Lincoln stories-some familiar and beloved, some fresh and unexpected- Looking for Lincoln in Illinois: Lincoln's Springfield is a carefully researched, richly illustrated guide to the Springfield, Illinois, locations on the Looking for Lincoln Story Trail. Created by the Looking for Lincoln Heritage Coalition, this trail consists of more than two hundred illustrated storyboards posted in sites of significance to Lincoln's life and career across fifty-two communities in Illinois. The storyboards connect Lincoln-related tales to the geographical locations whe.